PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN - ILHAM, MUKHAMAD (Jurnal Ilmu Manajemen (JIM), 2019)
This study aims to analyze the influence of work discipline and physical work environment on employee performance at PT. PLN (Persero) Rayon Porong. The approach used in this study is a quantitative approach. The population in this study were 58 employees and the sample used was 37 employees using purposive sampling because the sampling technique was based on specific criteria that were in accordance with the research objectives. The data analysis technique used is Partial Least Square with the help of SmartPLS 3.0 software. The results of this study indicate that work discipline influences employee performance with an estimate coefficient of 0,625 and a t-statistic of 6,441 which exceeds the t-table value with a value of 1.96. and the physical work environment has an effect on the performance of employees with an estimate coefficient of 0,360 and a t-statistic of 2,933 which is higher than the value of t-table with a value of 1,96. Keywords: employee performance, physycal work environment, work discipline.